The Future of the San Francisco System: Pressures and Prospects. Issue 1 (28th January 2020) - Teo, Sarah; Emmers, Ralf
Abstract : This article discusses the pressures on the San Francisco System, and argues that despite these challenges, the hub‐and‐spokes framework is likely to persist. While the impact of these pressures on individual alliances may vary, this system as a whole is expected to modify in three primary ways. Specifically, the San Francisco System is likely to become more diffused, selectively interconnected, as well as characterized by more insecurity toward the alliances on the part of both the United States and its allies. The worst‐case scenario for all U.S. regional allies would be being forced to choose between the United States and China. In this sense, the evolution of the U.S. hub‐and‐spokes system toward something that is more diffused and interconnected might, in the longer term, help allies to avoid such a situation amid increasing pressures. Abstract : 旧金山体制的未来：压力与前景: 本文探讨了旧金山体制面临的压力，并主张，尽管存在这些挑战，这一轴辐框架很有可能持续。虽然这些压力对个别联盟产生的影响可能存在差异，但这个体制作为一个整体被期望从三个主要方式进行调整。特别地，旧金山体制很有可能变得更为扩散、选择性地相互联系、以及对美国和其盟友而言，都存在对联盟的态度更为不安这一特征。对该地区所有的美国盟友而言最坏的场景则是，被强迫在美国和中国之间做选择。从这个意义上讲，美国的轴辐体制朝更为扩散和相互联系的方向发展，在长期看来，可能会帮助盟友在面临日益增加的压力情况下避免这一场景。 Abstract : El Futuro Del Sistema San Francisco: Presiones y Perspectivas: Este artículo discute las presiones sobre el Sistema de San Francisco y argumenta que a pesar de estos desafíos, es probable que el marco de centro y radios persista. Si bien el impacto de estas presiones en las alianzas individuales puede variar, se espera que este sistema en su conjunto se modifique de tres maneras principales. Específicamente, es probable que el Sistema de San Francisco se difunda, se interconecte selectivamente y se caracterice por una mayor inseguridad hacia las alianzas tanto de Estados Unidos como de sus aliados. El peor escenario para todos los aliados regionales de EE. UU. Se vería obligado a elegir entre Estados Unidos y China. En este sentido, la evolución del sistema de centros y radios de EE. UU. Hacia algo más difuso e interconectado podría, a largo plazo, ayudar a los aliados a evitar tal situación en medio de presiones crecientes.